Prevalence and Antibiotic Susceptibility of Bacterial Isolates From Dogs With Ulcerative Keratitis in Midwestern United States - Hewitt, Joshua S.; Allbaugh, Rachel A.; Kenne, Danielle E.; Sebbag, Lionel (Frontiers in Veterinary Science, 2020)
The objective of this study was to describe bacterial culture and antibiotic susceptibility results in 476 dogs presenting with suspected bacterial keratitis in Iowa and surrounding Midwestern states, further detailing trends in patient characteristics, seasonality, and antimicrobial resistance. Corneal swabs yielded 465 bacterial isolates and 220 cultures (46.2%) with no apparent growth (0-5 isolates per culture). The most frequent bacterial genera were Staphylococcus (32.3%), Streptococcus (19.1%), and Pseudomonas (12.5%), while the most common bacterial species were Staphylococcus pseudintermedius (26.7%), Streptococcus canis (12%) and Pseudomonas aeruginosa (7.5%). Compared to mixed-breed dogs, canine breeds most likely to be examined for ulcerative keratitis included Boston terrier, Cavalier King Charles spaniel, miniature pinscher, pug, rat terrier, Saint Bernard, shih tzu, and silky terriers. In summer, the likelihood to yield a negative culture was reduced while the likelihood to culture Pseudomonas species was increased. Bacteria considered multidrug resistant (MDR, resistant to ≥ 3 antibiotic classes) represented 20% of all canine isolates and were most prevalent for Staphylococcus species (33%). Analarming, escalating trend of MDR prevalence was noted between 2016 (5%) and 2020 (34%). Individual ophthalmic preparations (ie, single antibiotics or commercially available antibiotic combinations) with highest efficacy against all bacterial isolates included chloramphenicol (83%), ceftiofur (79%), amikacin (77%), neomycin-polymyxin B-bacitracin (77%), and gentamicin (74%). Efficacy of systemic antibiotics and combinations of ophthalmic preparations was also evaluated. Based on the present findings, triple antibiotic (Neo-Poly-Bac) is recommended as empirical monotherapy for prophylactic antibiotic therapy in dogs with simple corneal ulcers, while a chloramphenicol-ciprofloxacin combination is empirically recommended for therapeutic management of infected corneal ulcers pending culture and susceptibility results. Pending culture and susceptibility results, appropriate selection of empiric antibiotic therapy is important to enhance therapeutic outcome and reduce antibacterial resistance in dogs with corneal ulceration.